Violent Conflicts Increase Income Inequality - Marc Vothknecht (Weekly Report, 2009)
Political unrest, civil war, and - in extreme instances - genocide have contributed to the disappointing economic growth observed in many developing countries in recent decades, particularly in Africa. Sustained periods of violence also influence the distribution of income within a society; a cross-country analysis shows that income inequality increases as a result of violent conflicts, especially in the early post-war period. Immediate post-war efforts to address the social and economic disruption caused by conflict may help to counteract this trend.
Keywords: O11; O15; 330; Inequality; Conflict; War